Cross-Border Political Donations and Pareto-Efficient Tariffs - Masahiro Endoh (Yale University, Economic Growth Center, 2005)
This paper examines the effects of lobbying activities across international borders, on determining each countrys import tariff in a multi-principal, multi-agent, menu-auction model. Cross-border political donations could promote international policy cooperation because of two of their distinctive characteristics. First, special interest groups use cross-border donations as tools to wield their influence on ruling parties of other countries directly, which promotes efficiency of policy formation. Second, for ruling parties of countries, cross-border donations make them take into account the impact of their policy on other countries, which makes them more sensitive to other countries welfare and, therefore, more cooperative with others. When ruling parties estimate the worth of political contributions from national special interest groups and from foreign lobbying groups with the same weight, Pareto-efficient tariffs are attained at which world welfare is maximized.
Keywords: D72; F13; H21; P48; 330; Cross-border Donations; Truthful Equilibrium; Pareto-Efficient Tariffs; Interessenpolitik; Parteienfinanzierung; Zoll; Importbeschränkung; Pareto-Optimum; Theorie